2011
DOI: 10.1136/neurintsurg-2011-010147
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of emergency carotid artery stenting for a high-grade carotid stenosis with intraluminal thrombus under proximal flow control in hyperacute and acute stroke

Abstract: In stroke patients with a high-grade carotid stenosis with ILT, eCAS under PFC is safer and more effective in achieving a favorable clinical outcome than eCAS without PFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Of the 63 patients, 62 underwent CAS with the MSK-guide 7.5×90 (table 1) and the remaining patient underwent CAS with proximal flow control via the femoral route due to thrombi around the carotid stenosis 9. The 62 patients underwent transbrachial or transradial diagnostic angiography via the right-sided access route with a 3.2 Fr catheter (125 cm, 3.2 Fr MSK catheter; Medikit) in our institution, which demonstrated that they had a high-grade carotid stenosis and had no problems using the right brachial artery route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 63 patients, 62 underwent CAS with the MSK-guide 7.5×90 (table 1) and the remaining patient underwent CAS with proximal flow control via the femoral route due to thrombi around the carotid stenosis 9. The 62 patients underwent transbrachial or transradial diagnostic angiography via the right-sided access route with a 3.2 Fr catheter (125 cm, 3.2 Fr MSK catheter; Medikit) in our institution, which demonstrated that they had a high-grade carotid stenosis and had no problems using the right brachial artery route.…”
Section: Resultsmentioning
confidence: 99%
“…The current 6 Fr MSK-guide is not a balloon-guide catheter and cannot block proximal flow. This limits the application of the 6 Fr MSK-guide, which is not appropriate for patients in whom the flow reversal technique is required 9 16…”
Section: Discussionmentioning
confidence: 99%
“…When it was difficult for the devices to pass through the lesion, we transiently, usually <2 min, inflate the balloon to support their navigation to the distal area (figure 1B). The balloon-guiding catheter was also reported to be useful for those patients with carotid stenosis and intraluminal thrombi 11. The degree of carotid stenosis was assessed using cerebral digital subtraction angiography by the method reported in the North American Symptomatic Carotid Endarterectomy trial 12…”
Section: Methodsmentioning
confidence: 99%
“…However, there are relatively few reports describing outcomes of PTA and CAS for the treatment of carotid artery stenosis with an intraluminal thrombus. [6] In the NASCET study, Villarreal et al [3] reported that the 30-day risk of stroke or death for patients with an intraluminal thrombus was 12.0% and 10.7% for patients treated with surgery or medical therapy, respectively. Urgent carotid surgery versus percutaneous approach seems to be the most feasible option as in the present case.…”
Section: Discussionmentioning
confidence: 99%